Beauty and the beast : disney movie collection(big book) (Parragon UK, 2017)
"Beauty and the Beast Big Book" is a beautifully illustrated retelling of the classic fairy tale. The story follows Belle, a kind and adventurous young woman, who finds herself trapped in a mysterious castle with the Beast, a prince cursed to live in a monstrous form. As Belle discovers the Beast's gentle heart and learns the true meaning of love and sacrifice, the bond between them grows stronger. This enchanting tale explores themes of inner beauty, acceptance, and the transformative power of love, making it a timeless favorite for readers of all ages.